Pandemic populism: COVID-19 and the rise of the nationalist AUR party in Romania - Doiciar, Claudia; Cretan, Remus (Geographica Pannonica, 2021)
Many Central and Eastern European countries elected nationalist parties in the wake of the collapse of communism: a phenomenon often attributed to a combination of socioeconomic crisis and political instability. In 2010s, after the decay of other nationalist parties, Romania was seen as an exception to this rule, but the Covid-19 pandemic times have witnessed the rapid rise of a new nationalist party: the AUR (the Alliance for the Union of Romanians). Parliamentary elections in December 2020 saw this new political force gain 9.1% of the vote. Whereas previous nationalist parties in post-communist Romania tended to appeal to more senior/elderly voters, there is evidence that the AUR vote is strong amongst men under the age of 35 who are educated to an elementary or high school level. This paper uses national electoral data, media analysis, and in-depth interviews with young, educated people to explore the spatial distribution of AUR support, the ways in which the COVID-19 pandemic has assisted the party’s rise to prominence, and attitudes amongst university students to both the style and content of their politics. The paper concludes that the AUR offer a potent mix of old nationalism, religious faith, traditional family values and new ideological elements, such as environmentalism, anti-globalization, and anti-government critique to create a self-consciously ‘alternative’ political rhetoric. This is presented via new channels (especially social media) in a deliberately opportunistic, controversial, and spectacular manner. However, our investigation suggests that neither the content nor the style of this politics has widespread appeal to more educated younger voters.
Keywords: populism; COVID-19; nationalism; AUR; political party; Romania